Multiplex Ligation-Dependent Probe Amplification Accurately Detects Turner Syndrome in Girls with Short Stature - Grandone, Anna; Del Vecchio Blanco, Francesca; Torella, Annalaura; Caruso, Manuela; De Luca, Filippo; Di Mase, Raffaella; Messina, Maria Francesca; Salerno, Maria Carolina; Sallemi, Alessia; Perone, Lucia; Marzuillo, Pierluigi; Miraglia Del Giudice, Emanuele; et al. (Hormone research in paediatrics, 2016)
We aimed at evaluating a standard multiplex ligation-dependent probe amplification (MLPA) probe set for the detection of aneuploidy to diagnose Turner syndrome (TS). We first fixed an MLPA ratio cutoff able to detect all cases of TS in a pilot TS group. We then tested this value on a second group of TS patients and a short-stature population to measure specificity and sensitivity. 15 TS patients with X mosaicism or X structural abnormalities (Pilot TS Group), 45 TS karyotype-assessed patients (TS Group), and 74 prepubertal female patients with apparent idiopathic short stature (Short-Stature Group) were enrolled. All subjects underwent MLPA and karyotype analysis. In the TS and Short-Stature Groups, MLPA testing was performed in blind. The choice of an MLPA threshold ratio of 0.76 for at least 1 probe allowed us to detect all TS cases, including mosaicisms. Sensitivity and specificity were 100% (CI 95%, 0.92-1) and 88.89% (CI 95%, 0.79-0.94), respectively. The positive predictive value was 88.5%, and the negative predictive value was 100%. MLPA detected the presence of Y chromosome material in 2 patients. MLPA is an accurate and inexpensive tool to screen for TS in girls with short stature. A customized MLPA kit may be useful for the screening of an even larger population.